Galería de palabras : la variedad de la ecfrasis - Artigas Albarelli, Irene (México, D.F. : Universidad Nacional Autónoma de México : Bonilla Artigas Editores ; Madrid, España : Iberoamericana, 2013)
Essays exploring relationship between visual and literary arts. Revives and expands on age-old concept of ekphrasis, referring to rhetorical exercise offering dramatic description of work of art. Pairs and compares writers with artists of many cultures and time periods: William Carlos Williams and Seamus Heaney with Brueghel; Margaret Atwood with Manet; Joseph Cornell with Octavio Paz and Elizabeth Bishop; and others.
Incluye referencias bibliográficas (páginas 269-277).
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2019. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Art and literature; Literature, Modern -- History and criticism; Arte y literatura; Literatura Moderna -- Historia y crítica.; Libros electrónicos.